Analysis of academic knowledge about the code of ethics for medicine students developed by the Federal Medicine Council of Brazil - Khouri, Jussara Mathias Netto; Bahia, Lilian; de Bioética, Liga Acadêmica; Rêgo, Francisca Melo Pojal da Silva; Nunes, Rui Manuel Lopes (Acta Bioethica, 2024)
Introduction: In 2018, the Federal Council of Medicine (FCM), the regulatory body of the medical profession in Brazil, developed the Medical Student Code of Ethics (CEME), with the aim of positively influencing the conduct of future doctors through ethical and humanitarian training. Objective: The objective of this study was to identify whether medical students are aware and knowledgeable of the CEME. Materials and Methods: A field study was carried out with quantitative and cross-sectional approaches. Subjects were medical students in the 1st to the 12th semesters at a Brazilian university. Results: The survey results showed that most medical students (56%) did not know the CEME. Further, when examining individual classes, grouped as first years (M1 to M8) and last years (M9 to M12), only 30% of the students in the first group and 27% of the students in the last group were aware of the CEME. Conclusion: Most medical students, regardless of time in school, are unaware of the CEME.